ANALISIS AKUNTANSI PIUTANG DAGANG PADA PT. TRI BOS NUSANTARA PEKANBARU - Yusrizal Yusrizal; Ida Maryanti Silaban (Institut Bisnis dan Teknologi Pelita Indonesia, 2017)
This study discusses the account receivable accounting at PT. Tri Bos Nusantara Pekanbaru.The dependent variable in this research is the implementation of account receivable as stated in Statement of Financial Accounting Standards (SFAS), and the independent variable are the recording of accounting receivable, recognition and measurement of account receivable, appraisad of account receivable, and the statements of account receivable in the balance sheet. This research show that the account receivable on PT. Tri Bos Nusantara Pekanbaru has not fully met the standards of the Statement of Financial Accounting Standards (SFAS). The recording and the recorgnition of account receivable that had been done correctly by the company, but the measurement and appraisad of account receivable are not quite right, and there are also a mistake on the statements of account receivable in the balance sheet. Penelitian ini membahas mengenai akuntansi piutang dagang pada PT. Tri Bos Nusantara Pekanbaru. Adapun variabel terikat dalam penelitian ini adalah penerapan akuntansi piutang dagang menurut Pernyataan Standar Akuntansi Keuangan (PSAK), dan variabel bebasnya terdiri dari pencatatan piutang, pengakuan dan pengukuran piutang, penilaian piutang, dan penyajian piutang dineraca. Hasil penelitian menunjukkan bahwa perlakuan akuntansi piutang dagang pada PT. Tri Bos Nusantara Pekanbaru belum sepenuhnya sesuai dengan PSAK yang berlaku. Pencatatan dan pengakuan piutang yang dilakukan oleh perusahaan telah tepat, namun pengukuran dan pelaporan piutang masih kurang tepat, serta kesalahan dalam penyajian nilai piutang di neraca.